Progressive Muscle Relaxation and Dhikr on Reducing Post Traumatic Stress Disorder in Earthquake Victims - Sasmita, Heppi; Yanti, Nova; Hendri, Karnova; Tasman, Tasman; Astuti, Verra Widhi; Fadriyanti, Yessi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Post-Traumatic Stress Disorder (PTSD) is one of the mental health problems caused by the disaster. If it is not treated properly, it can lead to serious mental disorders. The purpose of this study was to determine the changes in signs and symptoms of PTSD in earthquake victims through progressive muscle relaxation (PMR) therapy and dhikr therapy. The study design was a quasi-experimental pretest-posttest with a control group with the intervention of PMR and dhikr therapy. The sample size was 40 people consisting of 20 intervention groups and 20 control groups taken by proportional simple random sampling technique. The results of the study were analyzed by dependent T-Test to see differences in PTSD signs and symptoms before and after intervention and paired t-test to see differences in PTSD signs and symptoms in each group. The statistical test results obtained a value of P-value less than 0.05, it can be concluded that there was a significant decrease between PTSD signs and symptoms of earthquake victims before and after the intervention of PMR and Dhikr Therapy in the control group. Signs and symptoms of PTSD in the earthquake disaster victims in the intervention group decreased significantly from the control group. Nurses in providing services to disaster victims who experience PTSD can apply PMR therapy and dhikr. It is necessary to socialize and optimize the application of PMR and dhikr for health workers.Abstrak: Post-Traumatic Stress Disorder (PTSD) merupakan masalah kesehatan mental yang dapat terjadi akibat bencana. Apabila tidak ditangani dengan serius, PTSD dapat mengakibatkan gangguan jiwa berat. Tujuan dari penelitian ini adalah untuk mengetahui perubahan tanda dan gejala PTSD pada korban bencana gempa melalui terapi proggressive muscle relaxation (PMR) dan dzikir pada kelompok intervensi dan kelompok kontrol di Kabupaten Solok Selatan. Penelitian ini menggunakan quasi expriemental pretest-posttest with contol group dengan intervensi terapi PMR dan dzikir. Sampel penelitian sebanyak 40 dengan 20 kelompok intervensi dan 20 kelompok kontrol yang diambil dengan Teknik proporsional simple random sampling. Hasil penelitian di Analisa dengan uji beda 2 mean yaitu uji dependent T-Test untuk melihat perbedaan tanda dan gejala PTSD sebelum dan sesudah intervensi dan paired t-test untuk melihat perbedaan tanda dan gejala PTSD pada masing-masing kelompok. Hasil analisis menunjukkan adanya penurunan yang bermakna antara tanda dan gejala PTSD korban bencana gempa sebelum dan sesudah intervensi PMR dan Dzikir pada kelompok control (P value kurang dari 0,05). Tanda dan gejala PTSD korban bencana gempa kelompok intervensi menurun secara bermakna dari kelompok kontrol.  Perawat dapat menerapakan terapi PMR dan dzikir untuk korban bencana yang mengalami PTSD. Perlu sosialisasi dan optimalisasi penerapan PMR dan dzikir tersebut bagi petugas kesehatan.